A Survey of Collaborative Web Search Practices - Morris, Meredith Ringel (Proceedings of CHI 2008, 2008)
Today's Web browsers provide limited support for rich information-seeking and information-sharing scenarios. A survey we conducted of 204 knowledge workers at a large technology company has revealed that a large proportion of users engage in searches that include collaborative activities. We present the results of the survey, and then review the implications of these findings for designing new Web search interfaces that provide tools for sharing.